Optimizing Capacity Building of Village Apparatus in Application-Based MSME Product Administration and Development Services in Pematang Serai Village, North Sumatra - Siahaan, Muhammad Donni Lesmana; Yusup, Mohammad; Harianto, Harianto (CV Raskha Media Group, 2025)
This study aims to examine how to optimize the capacity of village apparatus for administrative services and MSME product development in Pematang Serai Village, North Sumatra, through the use of technology-based applications. Pematang Serai Village faces challenges in improving the efficiency of administrative services and in developing the MSME sector, which is the primary economic source for the community. Therefore, this study proposes implementing an application-based system to simplify administrative processes and more effectively promote and manage MSME products. The method used in this study is a qualitative, descriptive approach, involving interviews with village officials, MSME actors, and other relevant parties. The results of the study show that with technology-based applications, the capacity of village apparatus in administrative services is increasing. At the same time, MSME actors can more easily and efficiently develop and market their products. This research is part of the Diktisaintek Berdampak program from the Ministry of Higher Education, Science, and Technology.